Experimental and numerical investigations into the behavior of circular concrete-filled double steel tubular slender columns. (15th September 2022) - Ci, Junchang; Ahmed, Mizan; Liang, Qing Quan; Chen, Shicai; Chen, Wensu; Sennah, Khaled; Hamoda, Ahmed
Research highlights: Test results on CCFDST short and slender columns under axial loading are presented. An efficient fiber model is developed for the simulation of CCFDST slender columns. The verified fiber model is used to investigate the responses of CCFDST slender columns. The applicability of codified methods to CCFDST slender columns is assessed. The numerical model and proposed design formulas are shown to yield accurate solutions. Abstract: This paper describes experimental and numerical investigations into the structural behavior of circular concrete-filled double steel tubular (CCFDST) slender columns loaded concentrically to failure. Test results on 8 specimens including 6 CCFDST slender columns and 2 CCFDST short columns are reported in this study that demonstrate the influences of column slenderness ratio and the thickness of the internal steel tube on the responses of CCFDST columns. A numerical model based on fiber analysis is developed to predict the axial load–deflection responses of CCFDST slender columns. The numerical model of CCFDST columns accounts for the effects of initial imperfection, concrete confinement, material nonlinearities and the interaction between axial load and deformations. A parametric study is performed by means of employing the verified computational technique to ascertain the sensitivity of the performance of CCFDST slender columns to various important parameters. Comparative analyses are undertaken to evaluate the applicability of Eurocode 4 and AISC 360–16 for conventional concrete-filled steel tubular columns (CFST) to CCFDST slender columns. It is shown that the developed numerical modeling technique simulates well the structural behavior of CCFDST slender columns and is an efficient computer simulation tool for the analysis and design of such composite columns. Moreover, the current design codes need to be modified to be utilized for designing CCFDST columns.